2020
DOI: 10.1590/0034-7167-2018-0757
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric analgesia in labor and its association with neonatal outcomes

Abstract: Objetive: To investigate the association between analgesia during labor and occurrence of neonatal outcomes. Method: Retrospective cohort study with medical records of 850 parturient. The exposure variable of interest was receiving pharmacological analgesia during labor and neonatal outcomes were: one- and five-minute Apgar, resuscitation maneuvers and referral of the newborn to Neonatal ICU. A logistic regression was carried out to obtain Odds Ratios and 95% confidence interval, with adjustment for confoundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…The severe pain of vaginal delivery [ 1 ] may cause negative emotions such as fear and worry, and may also result in syncope, weakness, and even fetal distress, cesarean section, and fetal death in severe cases [ 2 ]. Labor pain will elicit physiological stresses and perinatal complications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The severe pain of vaginal delivery [ 1 ] may cause negative emotions such as fear and worry, and may also result in syncope, weakness, and even fetal distress, cesarean section, and fetal death in severe cases [ 2 ]. Labor pain will elicit physiological stresses and perinatal complications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intraspinal nerve block anesthesia for labor analgesia features satisfactory nerve block and ideal analgesic effect, but the uncertainty of its effect on the labor process and the fetus has prevented its widespread implementation in China [ 5 ]. Epidural analgesia is associated with a significantly elevated incidence of intrapartum fever [ 2 ]. Intradural labor analgesia causes antepartum noninfectious fever, probably because epidural anesthesia dilates the limb vessels below the plane of anesthesia to increase convective radiation heat dissipation, and reduces skeletal muscle activity to decrease thermogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pesquisas que abordam a influência de intervenções obstétricas sobre o bem-estar fetal são iniciativas ainda recentes e não costumam estar associadas a tais intervenções e desfechos neonatais, Estas realizam apenas a análise dos modelos de atenção ao parto, de forma geral e suas repercussões nos resultados perinatais ou investigam o uso de intervenções de forma individualizada e sua associação aos desfechos neonatais ocorridos, tal como o explanado na pesquisa que traz a associação da analgesia no trabalho de parto à ocorrência de manobras de reanimação e encaminhamento para unidade de terapia intensiva neonatal (8)(9) . Portanto, busca-se aprofundar a compreensão sobre a implementação das práticas assistenciais no cenário do parto e nascimento, trazendo a associação dos resultados neonatais evidenciados em cada intervenção obstétrica utilizada.…”
Section: Introductionunclassified
“…Other studies reported that epidural analgesia might increase the negative outcome of neonates [9 ~ 11]. In terms of the analgesic effect on mothers and newborns, most of the studies compared different modalities of analgesia, only a few studies compared epidural analgesia speci cally vs. non-epidural labor [12,13]. To investigate if the epidural analgesia has any effects on maternal and neonatal outcomes, the baseline characteristics and overall outcomes of both mothers and newborns, including umbilical cord blood gas analysis, were performed in the present study.…”
Section: Introductionmentioning
confidence: 99%